SPEECH ACT IN STRANGER THINGS SEASON 3: A PRAGMATICS STUDY - Bagis, Haula; Mahyuni; Arafiq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Speech acts are a type of spoken language and part of pragmatics that occur in both verbal and nonverbal contexts. This study examines the use of speech acts by the characters in Stranger Things: Season 3, focusing on illocutionary acts as classified by Searle (1980), which include assertive, directive, commissive, expressive, and declarative speech acts. Using a descriptive qualitative approach, this research analyzes the speech acts found in the characters' utterances to determine their types, frequency, and relevance to characterization. The results indicate that all five types of speech acts appear in the series, assertive (36.18%), directive (36.64%), expressive (24.91%), commissive (1.87%), and declarative (0.40%). Assertive speech acts, which include stating, affirming, and describing, are frequently used by the main characters to convey information and theories. The presence of speech acts in Stranger Things: Season 3 is also consistent with the creative vision of the Duffer Brothers as directors.The high frequency of assertive and directive speech acts in the study illustrates how characters often face urgent situations that require immediate action, whether in confronting supernatural threats or navigating everyday social interactions. Overall, speech acts in Stranger Things: Season 3 shape character interactions and drive the plot, consistent with the Duffer Brothers' storytelling style.